BENTUK-BENTUK PENERAPAN METODE TAJRIBI DALAM MENGINTERNALISASI NILAI AKHLAK PESERTA DIDIK MIN 8 BONE DI ERA DIGITAL - Nurhikmah, Marwiah; Syarifuddin Ondeng; Andi Achruh; M. Muzakkir; Muh. Rusdi T (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This study examines the application of the tajribi method in internalizing moral values among students at MIN 8 Bone, Bone Regency. Using a qualitative field research approach, the study incorporates normative theological, pedagogical, and psychological perspectives to explore moral value internalization comprehensively. Data were gathered through observation, interviews, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. The findings show: The planning stage involves habituation activities, scheduling, and setting rules. Implementation focuses on simple, consistent daily activities suited to students’ abilities. Supporting factors include students’ interest, age, educators’ guidance, and parental involvement. Challenges stem from students’ lack of awareness, fatigue, limited facilities, time constraints, and environmental influences. The novelty of this research lies in employing the tajribi method as a sustainable approach that integrates parental and teacher collaboration in character building. Recommendations include leveraging technology to enhance the method's implementation in the digital era and providing educator training programs to optimize its role in moral education